Existence of fixed point and best proximity point of p-cyclic orbital phi-contraction map - Magadevan, Prabavathy; Karpagam, Saravanan; Karapınar, Erdal (Nonlinear Analysis: Modelling and Control, 2022)
In this manuscript, p-cyclic orbital ϕ-contraction map over closed, nonempty, convex subsets of a uniformly convex Banach space X possesses a unique best proximity point if the auxiliary function ϕ is strictly increasing. The given result unifies and extend some existing results in the related literature. We provide an illustrative example to indicate the validity of the observed result.